PENGARUH PEMBERIAN MADU DAN JINTAN HITAM TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS DI KLINIK PRATAMA BERTHA MABAR HILIR TAHUN 2024 - Purba, Tetty Junita; Siregar, GF Gustina (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
According to UNICEF 2020, breastfeeding is beneficial for both the mother and the child because it can assist in the brain development of the child, shield the child from infections, lower the risk of obesity and other diseases, and shield the mother from breast and ovarian cancer. In Indonesia, exclusive breastfeeding was only 67.9 percent in 2022, which is lower than the 69.7 percent breastfeeding coverage rate in 2021. This target has not yet met the national goal of implementing exclusive breastfeeding, which is 80 percent (WHO, 2023). Therefore, honey and black cumin must be given to try to increase breast milk production. At the Bertha Mabar Hilir clinic in 2024, the purpose of this study is to investigate the impact of administering honey and black cumin on the rate of breast milk production. This kind of research is quasi-experimental and uses a pretest- posttest design with only one group. Total sampling was done, with 12 mothers who had given birth on the 14th day. It was obtained from postpartum mothers whose breast milk did not flow smoothly before 7 people (58.4%) to after none (0%), and there was an increase in the mean value of 3.17 from postpartum mothers whose breast milk did flow smoothly before 5 people (41.6%) to after 12 people (100%). A p-value of (0.00) (0.05) was obtained from the Paired Simple T-test, indicating that giving honey and cumin to postpartum mothers significantly increased the production of breast milk.